2016
DOI: 10.3329/agric.v14i1.29096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Municipal Wastewater Irrigation on Yield and Fertilizer Requirement of Wheat (<i>Triticum aestivum</i> L.) in Bangladesh

Abstract: Due to increasing scarcity of fresh water, use of unconventional water source (e.g., wastewater) in irrigation has now become important. However, inclusive information on the effects of wastewater on crop production and soil health is necessary for such intervention. This study was designed to evaluate these effects by demonstrating the contribution of municipal wastewater (hereafter called wastewater) on yield and nutrient requirement of wheat (Triticum aestivum L.) cv Shatabdi. Five irrigation treatments  I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…The WW containing nutrients like NPK and micronutrients can increase the yield if used for irrigation. It was confirmed by other researchers that the biomass of wheat increased with the application of wastewater [ 17 ]. Similar results were established in another study [ 18 ] who reported the maximum biomass of soya bean with the combined use of NPK and city waste compost.…”
Section: Resultssupporting
confidence: 68%
“…The WW containing nutrients like NPK and micronutrients can increase the yield if used for irrigation. It was confirmed by other researchers that the biomass of wheat increased with the application of wastewater [ 17 ]. Similar results were established in another study [ 18 ] who reported the maximum biomass of soya bean with the combined use of NPK and city waste compost.…”
Section: Resultssupporting
confidence: 68%
“…Since long ago municipal wastewater has been used due to the abundance of nutrients and essential elements for crop growth and soil fertility. [10] , [11]. The physical and chemical properties of water and soil are affected by the discharge of untreated wastewater as it enters the food chain and affects agricultural products and human and animal health.…”
Section: -Introductionmentioning
confidence: 99%